2016
DOI: 10.1016/j.injury.2016.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Substantial accuracy of fracture classification in the Swedish Fracture Register: Evaluation of AO/OTA-classification in 152 ankle fractures

Abstract: The study results show substantial agreement between classifications made in the SFR and gold standard classification. The finding is equivalent to or higher than in previous studies. Consequently, we conclude that classifications of ankle fractures in the SFR are accurate and valid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 10 publications
1
32
0
1
Order By: Relevance
“…In the SFR, fractures are classified according to the Arbeitsgemeinschaft für Osteosynthesefragen/ Orthopaedic Trauma Association (AO/OTA) classification system [23]. Several studies have shown that this data has a high accuracy and validity [24][25][26][27]. The total number of orthopaedic departments in Sweden is 54.…”
Section: Study Population and Data Collectionmentioning
confidence: 99%
“…In the SFR, fractures are classified according to the Arbeitsgemeinschaft für Osteosynthesefragen/ Orthopaedic Trauma Association (AO/OTA) classification system [23]. Several studies have shown that this data has a high accuracy and validity [24][25][26][27]. The total number of orthopaedic departments in Sweden is 54.…”
Section: Study Population and Data Collectionmentioning
confidence: 99%
“…Na literatura encontramos trabalhos que avaliaram a variação na classificação intra e entre observadores das fraturas de tornozelo. Todos os estudos encontrados utilizaram o coeficiente Kappa para a análise da concordância, mostrando-se o mais confiável para se fazer a pesquisa (18)(19)(20)(21)(22)(23) . Na literatura brasileira foram encontrados quatro estudos que fizeram uma análise semelhante (7,12,24,25) .…”
Section: Discussionunclassified
“…Initially, an extensive literature research was conducted, using PubMed 3 , MEDLINE, Google Established registries used varying methods to evaluate their data quality, ranging from reproducibility of entered data sheets on cases 16 , completeness and correctness of registered procedures and diagnoses 8,13,18 up to plausibility of entered datasets 5 . No two registries had entirely matching approaches to data validation and no standardized systematic using transparent and reproducible methods could be identified.…”
Section: Finding a Methods For Data Quality Assessmentmentioning
confidence: 99%